La percezione disturbata e le sue conseguenze in «Almost blue» di Carlo Lucarelli - Kornacka, Barbara (Wydawnictwo Naukowe UAM, 2008)
Distorted Perception and its Consequences in «Almost Blue», a Novel by Carlo Lucarelli is an article which deals with an analysis and description of the three main characters from the perspective of their sensory perception of reality. In each analysed case the main characters' experiences are distorted (damaged, misinterpreted) due to blindness, mental disease or Premenstrual Syndrome. The distorted sensory perception affects their contact with reality and their understanding of certain phenomena. Their individual human corporality changes the sense of reality.
Distorted Perception and its Consequences in «Almost Blue», a Novel by Carlo Lucarelli
Keywords: Lucarelli Carlo; Almost Blue